2014
DOI: 10.1073/pnas.1324118111
|View full text |Cite
|
Sign up to set email alerts
|

Rich-club organization of the newborn human brain

Abstract: Combining diffusion magnetic resonance imaging and network analysis in the adult human brain has identified a set of highly connected cortical hubs that form a "rich club"-a high-cost, highcapacity backbone thought to enable efficient network communication. Rich-club architecture appears to be a persistent feature of the mature mammalian brain, but it is not known when this structure emerges during human development. In this longitudinal study we chart the emergence of structural organization in mid to late ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

45
338
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 333 publications
(388 citation statements)
references
References 70 publications
45
338
3
2
Order By: Relevance
“…We show for the first time, to our knowledge, that, already by the time of normal birth, the topographical organization of functional thalamocortical connectivity defined by strongest connectivity is consistent with current information on the adult brain using tracer methods (25)(26)(27)(28)(29)(30), diffusion studies (15,16), and functional imaging in adult subjects (18). These results add to the growing evidence of the maturity of the human brain by the time of normal birth (12,31,32).…”
Section: Discussionsupporting
confidence: 85%
“…We show for the first time, to our knowledge, that, already by the time of normal birth, the topographical organization of functional thalamocortical connectivity defined by strongest connectivity is consistent with current information on the adult brain using tracer methods (25)(26)(27)(28)(29)(30), diffusion studies (15,16), and functional imaging in adult subjects (18). These results add to the growing evidence of the maturity of the human brain by the time of normal birth (12,31,32).…”
Section: Discussionsupporting
confidence: 85%
“…Although many aspects of gene expression in the brain show a developmentally persistent profile (35), it is unclear whether the same transcriptional signature of hub connectivity would be apparent throughout development. Although rich club connectivity seems to be established early in development (2,36), it also undergoes significant remodeling later in life (37). Interestingly, recent evidence indicates that aerobic glycolysis plays a prominent role in biosynthesis and growth and that it accounts for a larger fraction of the brain's energetic needs earlier in development, peaking in early childhood when levels of synaptic development are highest (35).…”
Section: Discussionmentioning
confidence: 99%
“…The structural connectomes defined in the previous section are networks and it has become popular to examine these networks using various network measures [2,32,40,44,47,58]. The collection of network measures used here are given in Table 2.…”
Section: Network Analysismentioning
confidence: 99%
“…Tymofiyeva et al used an atlas-free approach to analyze connectome development in preterm infants, children and adults, also employing network measures to capture topological changes [52,53]. Very recently, Ball et al studied a specific network measure known as rich-club organization in a cohort of preterm infants [2]. They found that this rich-club structure, known to be present in adult brain networks, emerges as early as 30 weeks PMA.…”
Section: Introductionmentioning
confidence: 99%